The complete mitochondrial genome of Cynops cyanurus chuxiongensis (Caudata: Salamandridae). Issue 1 (2nd January 2020) - Cui, Lin; Han, Fuyao; Li, Diyan; Fan, Xiaolan; Yang, Mingyao; Yang, Deying; Ni, Qingyong; Li, Yan; Yao, Yongfang; Xu, Huailiang; Zeng, Bo; Li, Ying; et al.
Abstract: Cynops cyanurus chuxiongensis is distributed in Yunnan plateau. In this paper, we sequenced and determined the complete mitochondrial genome of C. c. chuxiongensis. The assembled mitogenome is 16, 465 bp in length and encoding 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA genes (12S rRNA and 16S rRNA), and one control region (D-loop). The phylogenetic trees indicated C. c. chuxiongensis (KY418068) has the closest relationship with C. orientalis + C. orphicus, and clustered within the clade of genus Cynops.